Investigating the Effect of Group Social Work Development Method on Older Adult\'s Quality of Life and General Health, Focusing on Life Skill\'s Education, at Tehran Elderly Center - Marzieh Mirzayi; Mostafa Eghlimi; Ghoncheh Raheb; Maliheh Arshi (University of Social Welfare & Rehabilitation Sciences, 2012)
Objectives: today, older people population ratio is increasing in the world and as the same in our country. So, it is important to investigating the effective parameters that can effects old people quality of life and general health in order to edit major strategies of hygienic and welfare. This study aimed to determine the influence of group social work focusing on life skill education to improve elderly quality of life and general health on older adults attending Tehran elderly cultural center in 2011. Methods & Materials: in this semi-experimental study among to older people aged over 60 using targeted sampling method. The data collected using demographic questionnaire, sf-36 quality of life and ghq-28 general health using a pretest and posttest method, before and after attending at 10 sessions of life skills education with interference attitude due to group development model. Results: based on the results of dependent and independent t-test, quality of life was considerably different among men and women, although women had higher level of quality of life. Also, general health improved significantly in the two-sexual group. The effect of interference on study sample was demonstrated significantly higher level of older people quality average after participate in educational period comparing before it. And the older people general health average meaningfully increased after attending sessions too (comparing before it). Conclusions: generally, among study testable in comparison, the two-sexual group benefit of similar general health and difference quality of life. There was also a positive effect of life skills education attitude on quality of life and testable general health and in both sexual group while using group developmental social work view.